Preliminary Phytochemical And In Vitro Antioxidant Perspectives Of The Leaf Extracts Of Azima Tetracantha Lam ( Family : Salvadoraceae) - P.MUTHUSWAMY,; S.ELAKKIYA,; K.MANJUPRIYA,; K.DEEPA,; S.RAMACHANDRAN,; P.SHANUMGAPANDIYAN, (International Journal of Pharma and Bio Sciences, 2012)
Antioxidants are widely used as ingredients in dietary supplements such as superoxide dismutase,ferritin,ascorbic acid. Free radicals oxidation has been implicated in artherosclerosis , cancer occurring in lung, breasts, mouth, skin etc, neurodegenerative disease and imflammatory bowel disease. These above facts paved way to discover a new drug from the selected plant with multiple benefits. The present study was to evaluate the preliminary phytochemical screening,invitro and antioxidant activity of leaf extract of Azima tetracantha Lam. The plants were collected, authenticated, extracted by hot percolation and various extractive values such as petroleum ether soluble extractives, ethylacetate soluble extractives, methanol soluble extractives were performed. The fluorescence analysis was done by the UV absorption method, phytochemical screening of the plant was done for the estimation of total amount of alkaloid and flavanoids. The antioxidant studies was performed by the thiocyanate method. The free radical scavenging activity of the different fractions of methanol and ethyl acetate extracts of Azima tetracantha Lam was measured using DPPH employing the method of Blois. The superoxide anion scavenging activity of the different fractions of methanol and ethyl acetate extracts of Azima tetracantha Lam was performed by Chang. The hydroxyl radical scavenging activity was performed by the method of Kunchandy and Rao. It shows that it possess significant scavenging effect on the free radicals and inhibits peroxidation of lipid components and thereby acts as in effective antioxidant principle. Both methanol and ethyl acetate inhibit the LPO, DPPH, superoxide anion, hydroxyl radical. Ethyl acetate extract posses moderate activity when compared with the activity of ascorbic acid, BHT , Quercetin.